2017
DOI: 10.18410/jebmh/2017/1072
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Eye Donation Among Medical Students

Abstract: BACKGROUND The blindness due to corneal aetiology accounts for 0.9% of blindness in India. Corneal transplantation is the major treatment option for them. The lower rate of eye donation is the major obstacle to this procedure. Twenty-two thousand eyes are collected every year in India, which only serve half the requirement of corneal transplantations. Medical students who are future medical practitioners can be a good motivator for this eye donation. MATERIALS AND METHODS To assess the awareness of eye donatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This questionnaire is designed referring various publications related to eye donation. [7][8][9] A note of the use of information only for research purposes in mentioned clearly in the questionnaire. The questionnaire includes three sections.…”
Section: Methodsmentioning
confidence: 99%
“…This questionnaire is designed referring various publications related to eye donation. [7][8][9] A note of the use of information only for research purposes in mentioned clearly in the questionnaire. The questionnaire includes three sections.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the current participants demonstrated a decreased level of knowledge in many areas compared to other international studies, as the participants performed poorly in the knowledge test. 19 , 25 Data from the current study showed that relying only on media to increase the knowledge of medical students regarding eye donation is not sufficient. Therefore, including different curative and preventative features of corneal blindness through basic eye health care in the curriculum is greatly needed.…”
Section: Discussionmentioning
confidence: 66%
“…For instance, only 18% of the study participants knew that the perfect time for donation is within 6 hours after death, while similar study reported higher level of knowledge among students (68.7%). 19 Besides, the mean score of the participants in the test of background knowledge was just 3.24 out of 12 that shows profound lack of knowledge regarding eye donation in our study participants.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations